2014
DOI: 10.1016/j.yjmcc.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Functional importance of cardiac enhancer-associated noncoding RNAs in heart development and disease

Abstract: The key information processing units within gene regulatory networks are enhancers. Enhancer activity is associated with the production of tissue-specific noncoding RNAs, yet the existence of such transcripts during cardiac development has not been established. Using an integrated genomic approach, we demonstrate that fetal cardiac enhancers generate long noncoding RNAs (IncRNAs) during cardiac differentiation and morphogenesis. Enhancer expression correlates with the emergence of active enhancer chromatin sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 57 publications
(106 reference statements)
2
104
0
Order By: Relevance
“…Interestingly, the alteration of H19 and IGF2 coexpression is associated with RMS in humans (89). In addition to eRNAs in skeletal muscle, many eRNAs have been identified in cardiac development that are deregulated in several different cardiomyopathies (90,91). Overall, these findings place eRNAs at the top of a molecular hierarchy regulating myogenesis and predict their possible participation in muscle diseases as a result of mutations and/or altered expression (92).…”
Section: Circulating Ncrnas As Biomarkersmentioning
confidence: 97%
“…Interestingly, the alteration of H19 and IGF2 coexpression is associated with RMS in humans (89). In addition to eRNAs in skeletal muscle, many eRNAs have been identified in cardiac development that are deregulated in several different cardiomyopathies (90,91). Overall, these findings place eRNAs at the top of a molecular hierarchy regulating myogenesis and predict their possible participation in muscle diseases as a result of mutations and/or altered expression (92).…”
Section: Circulating Ncrnas As Biomarkersmentioning
confidence: 97%
“…LncRNAs were once regarded as transcriptional "noise" or cloning artifacts because of their absence of protein-encoding ability (6). Emerging evidence has indicated that aberrant expression of lncRNAs is associated with numerous diseases, including diabetes (7,8). Importantly, lncRNAs were shown to act as regulators of tumorigenesis via participating in biologic processes, such as modulation of apoptosis, proliferation, drug resistance, and the epithelial-mesenchymal transition process (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of lncRNAs have been found to be cardiac-specific during development or in pathological conditions, although their function needs further studies [50,51]. Forty lncRNAs involved in the lateral plate mesoderm formation and cardiomyocyte differentiation were observed to be differentially expressed during embryonic carcinoma cell differentiation into cardiac myocytes [52].…”
Section: Lncrnas and Cardiac Developmentmentioning
confidence: 99%
“…-132 and -172) expressed during cardiomyocyte differentiation of murine embryonic stem cells [50]. Four of these elncRNAs (mm67, -85, -130 and -132) appear to be evolutionary conserved in humans.…”
Section: Moreover Ounzain Et Al Identified Seven Elncrnas (Mm67 -7mentioning
confidence: 99%
See 1 more Smart Citation